Credit-Induced Boom-Bust Cycle in Nepal - Panthi, Santosh; Katuwal, Khagendra (Economic Journal of Nepal, 2024)
Credit to the private sector has been expanding rapidly in Nepal, yet the real sector's growth has remained sluggish. If credit expansion continues to grow faster than the real sector, the existing vulnerability could become a systemic risk for the broader economic system, potentially leading to an economic slowdown characterized by the boom-bust cycle. This study examines how sectoral credit allocation influences macroeconomic outcomes, particularly real GDP growth and inflation, by employing the Local Projections Approach to Impulse Response Functions (LP-IRFs)- a robust technique that estimates the dynamic responses of variables without assuming a specific structural model, offering flexibility and reliability over traditional VAR methods. Using quarterly time-series data for 67 observations from FY 2006/07Q4 to FY 2023/24Q2, the study finds that the rapid expansion of private-sector credit will ultimately lead to an economic slowdown. Specifically, credit concentrated in the non-tradable sector predicts lower output and higher inflation, thereby increasing the risk of economic downturns. Conversely, credit directed toward the tradable sector supports sustained economic growth and stable prices. The findings suggest that sectoral allocation of credit plays a critical role in determining macroeconomic boom-bust cycles. Policy recommendations include improving regulatory oversight and redirecting credit toward tradable sectors to mitigate financial vulnerabilities and enhance long-term growth prospects.